A trust model for remittance over a blockchain. (7th January 2022) - Lutete, Thomas Maketa; Zhang, Kaiwan; April, Alain; Shahzad, Aamir
Remittance is a global service used to transfer money to family and friends. Throughout the world, many companies offer remittance service to families who depend on it for their livelihood. However, the current service of remittance, as provided by remittance companies across the world, assume that the recipient will use the remitted funds for the purpose intended by the sender, such as paying for school fees, medical procedures or groceries. Thus, the current model stops handling the remittance transaction as soon as the beneficiary collects the money. The current service of remittance model does not enforce correct usage of the remittance's funds. This paper proposes a new blockchain and smart contract based remittance trust model that fully considers all the steps, and the stakeholders, necessary to ensure correctness of a remittance transaction: sending the money, acquiring a service, paying a service or refunding the money.